2023
DOI: 10.3389/fmicb.2023.1075557
|View full text |Cite
|
Sign up to set email alerts
|

8-HQA adjusts the number and diversity of bacteria in the gut microbiome of Spodoptera littoralis

Abstract: Quinolinic carboxylic acids are known for their metal ion chelating properties in insects, plants and bacteria. The larval stages of the lepidopteran pest, Spodoptera littoralis, produce 8-hydroxyquinoline-2-carboxylic acid (8-HQA) in high concentrations from tryptophan in the diet. At the same time, the larval midgut is known to harbor a bacterial population. The motivation behind the work was to investigate whether 8-HQA is controlling the bacterial community in the gut by regulating the concentration of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Lepidopterans are also known to host a range of microbes, with bacteria mainly inhabiting the gut lumen [12,13]. Early studies on the microbial association with the lepidopteran gut disbelieved the existence of intimate microbial partnerships [14], but several other studies with lepidopteran larvae have demonstrated that gut bacteria can aid in food digestion [15], provide nutrients [16] and antimicrobials to regulate pathogens in the host gut microbiota [17] and participate in the metabolization of host plant-derived defense molecules [18,19] and pesticides [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Lepidopterans are also known to host a range of microbes, with bacteria mainly inhabiting the gut lumen [12,13]. Early studies on the microbial association with the lepidopteran gut disbelieved the existence of intimate microbial partnerships [14], but several other studies with lepidopteran larvae have demonstrated that gut bacteria can aid in food digestion [15], provide nutrients [16] and antimicrobials to regulate pathogens in the host gut microbiota [17] and participate in the metabolization of host plant-derived defense molecules [18,19] and pesticides [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent research on lepidopteran larvae has demonstrated that gut bacteria play crucial roles in food digestion facilitation [15], nutrient absorption enhancement [12], and direct contribution to host nutrition through production of essential nutrients (eg, L-tryptophan) [16]. Yet, gut bacteria of lepidopteran larvae can inhibit potentially harmful microorganisms by producing antimicrobial compounds [17] and reduce the toxicity of xenobiotics by the metabolization of host plantderived defense molecules [18,19] and pesticides [20][21][22].…”
Section: Introductionmentioning
confidence: 99%